The Effect of Applying Blockchain to The Accounting and Auditing - Iman Supriadi (Ilomata International Journal of Tax and Accounting, 2020)
Blockchain provides a extreme brand-brand new method towards document, procedure, as well as keep monetary info and deals. It has actually the prospective towards essentially alter the yard of the bookkeeping occupation as well as improve business community. Within this particular short post, our team talk about the ramifications of Blockchain in the business of bookkeeping as well as bookkeeping. Using a blockchain can help provide clarity on asset ownership and the existence of liabilities, and can dramatically increase efficiency for an accountant. Blockchain offers the potential for accounting and auditing. Blockchain helps auditors to track an account. Blockchain technology for auditors has conducted audit traces that they follow. For an accountant, Blockchain helps reconcile, trace the ownership of assets and authenticate transactions through features found in the technology. Blockchain can be used as a source of verification for data reported by accountants to users of the information generated by accounting